Volatility-adjusted 60/40 versus 100: New risk investing paradigm - Jim Kyung-Soo Liew; Ahmad Ajakh (Journal of Risk and Financial Management, 2020)
In this study we examine the volatility-adjusted 60/40 rule at the individual company level. We document that strong diversification benefits exist over the long-term, and that both the equity and corporate bonds exhibit positive expected drifts. For our sample of 30 large-cap companies, given that corporate bond positions have shown less volatility than the equity position, we leveraged the resultant portfolio of 60/40 to match that of the equity position. When we compare the two investments, we document an outperformance of 100 to 200 bps per year, even after we account for the leverage costs of 100 bps. We believe our work will open up a new risk investing paradigm for those seeking long-term advantages.
Keywords: 330; finance; leverage; 60/40; corporate bonds; equities; investments; new risk paradigm; performance; portfolio